Length - Weight Relationship and Condition Factor of Three Commercial Fish Species in Juba- South Sudan. - Obany Okuki Deng,; James Drfoun Amol AJAK,; Goang, O.M. Ayul, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
This study aimed to inspect the length-weight relationship and condition factors of three commercial fish species, Distichodus niloticus, Oreochromis niloticus, Heterotis niloticus in Juba, South Sudan. A total of 1800 fish specimens were collected from Juba fish landing sites during the study. Length-weight relationship, a and b were estimated. The means length for Distichodus niloticus, Heterotis niloticus, Oreochromis niloticus were 51.24±11.78, 57.66±13.91, and 34.96±4.10cm, respectively, and means weight were 306 ± 828.67, 2488 ± 962.91, and 1550 ±370.69g, respectively. Length weight relationship slope (b) value ranged from 1.70, 1.60 and 1.55, respectively.  All the fish species in the study showed negative allometries b less than 3, and the condition factor, k, ranged from 1.80±0.53, 1.40±0.51, and 3.63±0.34 for Distichodus niloticus, Heterotis niloticus, Oreochromis niloticus, respectively. K values greater than 0.5, indicated that the fish species were in good condition during the study period. Therefore, more study on length-weight and condition factor for all commercial fish species all over South Sudan is recommended for effective stock management and monitoring in freshwater bodies within the country.